Strategi Manajemen Antrean Di Taman Mini Indonesia Indah Terhadap Kepuasan Wisatawan - Sukesi, Ajeng Aspuan; Nugraha, Rizki Nurul (Peneliti.net, 2024)
The purpose of this study is to conduct an analysis of queue management on traveler satisfaction in Taman Mini Indonesia Indah. data analysis was carried out by sending questionnaires to 100 respondents from the Taman Mini Indonesia Indah. The data analysis technique employs advanced regression analysis and the application Statistical Product and Service Solution ( SPPS ) version 26.0. The result of this study use of the test method for testing vadility on the variables queue management (X) and tourist satisfaction (Y) show that all of the result were signifacnt at the level of 0,05. The number of variables in then n – 100 range with a signifacnt level 0,05 is 0,196, hence all of the variables are considered legitimate. Based on the result of the study, the management strategy for queue has positive effects on the condition of tourist satisfaction.